2022
DOI: 10.1007/s10802-022-00926-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Perpetuation of Cyberbullying Victimization in Adolescents: The Role of Executive Functions

Abstract: The consequences of cyberbullying victimization can lead to its perpetuation over time, initiating a vicious cycle. Thus, it is important to identify the factors that contribute to the persistence of victimization. This study aimed to examine some longitudinal mechanisms involved in the perpetuation of cyberbullying victimization in adolescents. The secondary aim was to study the protective role of executive functions (cognitive flexibility and selective attention) in this process, filling a gap in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…Consistent with previous research (e.g., Choi & Park, 2021;Lozano-Blasco et al, 2020;Morea & Calvete, 2022), a strong association was found between victimization and perpetration. This association was moderated by the interaction between T and C for both online and offline aggression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous research (e.g., Choi & Park, 2021;Lozano-Blasco et al, 2020;Morea & Calvete, 2022), a strong association was found between victimization and perpetration. This association was moderated by the interaction between T and C for both online and offline aggression.…”
Section: Discussionsupporting
confidence: 91%
“…Another limitation concerns the exclusive use of self-reports for the assessment of victimization and aggression measures, which could have contributed to the high association between the two variables due to shared variance. Although several studies have obtained high correlations between peer victimization and perpetration (Choi & Park, 2021;Morea & Calvete, 2022;Walters, 2021), it would be beneficial for future studies to also include reports from others (peers and teachers reports).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machado et al (2022) señalan al respecto, que los adolescentes son más propensos a sufrir diferentes tipos de ciberviolencia, puesto que son los principales usuarios de las TIC en sus actividades diarias. Por otra parte, es posible que la mayor vulnerabilidad de los adolescentes hacia la CVN, se deba a que aún se encuentran en desarrollo sus funciones ejecutivas, lo que los haría más propensos a tener dificultades para comprender y manejar las situaciones conflictivas de manera adecuada (Morea & Calvete, 2022). Además, los adolescentes son más influenciables a los comportamientos de sus pares y los que se transmiten a través de medios de comunicación y en redes sociales, por lo que es posible que perciban como normales aquellos comportamientos agresivos y de control de la pareja observados en sus pares y los que observan a través de esos medios (McLoughlin et al, 2020).…”
Section: Discussionunclassified